The Witch-Hunt; or, The Triumph of Morality - Bailey, F. G. (Frederick George) (Book collections on Project MUSE., 1994)
"Bailey moves easily between fieldnotes and memory as he takes a new look at his first impressions and reflects on what he has learned. His elegant book is a powerful reassessment of anthropology's most enduring themes and debates which will imprint on the reader's mind a vivid image of a place and its people."--Jacket